A comparison of prism adaptation with terminal versus concurrent exposure on sensorimotor changes and spatial neglect. Issue 4 (20th April 2020) - Facchin, Alessio; Bultitude, Janet H.; Mornati, Giulia; Peverelli, Milena; Daini, Roberta
ABSTRACT: Prism adaptation (PA) is a technique that induces a temporary change of the alignment between different reference frames. This technique has been shown to reduce many signs of unilateral spatial neglect (USN). Two procedures of prism adaptation have been used. In concurrent exposure participants can see their arm and hand during the movement trajectory, and during terminal exposure, participants can see only the most distal few centimetres. Because the two exposures elicit different proportions of visual and proprioceptive realignment, they could present different rehabilitation efficacies. We compared these procedures in 12 USN patients and 12 healthy participants who performed one session of PA with concurrent exposure and one session with terminal exposure. We compared the effects of the two exposure types on sensorimotor outcomes (visual subjective straight ahead, proprioceptive subjective straight ahead, open loop pointing, and error correction during exposure) and neglect outcomes. We found no significant differences in the effects of the two exposure types on sensorimotor performance of patients and controls, nor on patients' neuropsychological outcomes. Compared with controls, USN patients showed a significant rightward bias in visual subjective straight ahead pre-adaptation, a slower rate of error correction during prism exposure, and some evidence that visual and proprioceptive shift could be influenced by their neglect. Based on these results, we recommend that prism adaptation be conducted with concurrent exposure for easiness of execution.